Sport and physical activity during school recess for fifth grade Students at The Columbus School in Envigado municipality. (2023)
During school recess, challenging attitudes that affect students' social relationships often manifest. Therefore, this research project aims to identify students' perceptions regarding sports and physical activities, specifically during school recess. The methodology used employs a qualitative approach with a descriptive scope through surveys of the children and interviews with teachers. The sample consisted of fifth-grade students from the elementary section of The Columbus School in Medellín Municipality. The results indicate restrictions imposed by academic authorities on the use of ball games, with students using break time solely to converse with their peers and engage in video games. Activities with low impact during school recess are preferred. In conclusion, it is recommended to utilize recess hours for sports activities, promote active lifestyles through physical activity, enhance social skills through playful and recreational activities, leading to cognitive, mental, and social well-being.